1969
DOI: 10.48213/travessia.i70.253
|View full text |Cite
|
Sign up to set email alerts
|

Migrações e segmentação do mercado de trabalho O caso da migração brasileira para Portugal

Abstract: Neste texto são revistos os padrões de inserção dos migrantes brasileiros no mercado de trabalho em Portugal. É argumentado que as oportunidades laborais disponíveis se encontram, na maior parte dos casos, entre os segmentos menos atrativos do mercado de trabalho e que predominam situações de precariedade laboral. A concentração naqueles segmentos prejudica as possibilidades de integração plena na sociedade portuguesa. Esta evidência decorre da observação de algumas variáveis relacionadas com o emprego (partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Various of these neighbourhoods are characterised by the predominance of populations of African origin, sometimes with higher concentrations of one or another nationality in particular. As a number of research projects on immigrant employment patterns have demonstrated, from the very beginning, a significant part of the adult men of these neighbourhoods work in civil construction, while the women are above all employed in cleaning services of private houses, hotels or restaurants (see Cerdeira et al 2013;Machado, 2008;Rosales et al 2009;Peixoto, 2008;among others). In these peripheral contexts, daily street forms of socialisation perform a central role for all generations.…”
Section: African Immigration and Black Territories In Lisbonmentioning
confidence: 99%
“…Various of these neighbourhoods are characterised by the predominance of populations of African origin, sometimes with higher concentrations of one or another nationality in particular. As a number of research projects on immigrant employment patterns have demonstrated, from the very beginning, a significant part of the adult men of these neighbourhoods work in civil construction, while the women are above all employed in cleaning services of private houses, hotels or restaurants (see Cerdeira et al 2013;Machado, 2008;Rosales et al 2009;Peixoto, 2008;among others). In these peripheral contexts, daily street forms of socialisation perform a central role for all generations.…”
Section: African Immigration and Black Territories In Lisbonmentioning
confidence: 99%